1984
DOI: 10.2307/3576328
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity of Vascular Tissue: II. Differential Radiosensitivity of Aortic Cells in Vitro

Abstract: The cellular outgrowths from three layers of rabbit and monkey aorta were used as primary cultures. Irradiation of the tissue fragments at the time of explanation resulted in a reduction in outgrowth of 50% with a dose of 200 rad, and in a reduction of over 90% with doses of 300 rad and above. When comparable cultures were irradiated after 2 months in vitro as a mature actively metabolizing but slowly proliferating cell population, radioresistance was increased. Subcultures of medial smooth muscle cells irradi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 10 publications
1
15
0
2
Order By: Relevance
“…As shown in Figure 1D, mean I/M ratio was significantly higher in BMT mice tended to be lower than those of Smad3-null and wild-type mice, respectively, presumably due to the effect of vascular irradiation. 35,36 Representative cross sections of BMT null3wild and BMT wild3null femoral arteries are shown in Figure 1E and 1F. …”
mentioning
confidence: 99%
“…As shown in Figure 1D, mean I/M ratio was significantly higher in BMT mice tended to be lower than those of Smad3-null and wild-type mice, respectively, presumably due to the effect of vascular irradiation. 35,36 Representative cross sections of BMT null3wild and BMT wild3null femoral arteries are shown in Figure 1E and 1F. …”
mentioning
confidence: 99%
“…Weder Endothel-noch glatte Muskelzellen zeichnen sich durch eine auBergew0hnliche Strahlenreaktion aus [5,47] Insgesamt ist die Vulnerabilit5t einzelner Zellen entscheidend von der Zellzyklusphase abh~ngig [11,54]. Um die Strahlenbiologie besser verstehen zu k6nnen, ist es jedoch wichtig, genaue Dosisfindungsstudien durchzufª [2].…”
Section: Strahlenbioiogieunclassified
“…Experimentelle Arbeiten zeigen, daB die Zellen besonders in der G2/M-Zellteilungsphase empfindtich sind [11,12,22]. Es ist jedoch unktar, wann die verletzten Intimazellen der Gef~6wand in die proliferative Phase eintreten.…”
Section: Dosis-wirkungs-beziehungunclassified
“…13,14,15,16 In vitro studies had demonstrated the inhibition of proliferation of arterial smooth muscle cells (SMC's) and fibroblasts as well as decreased collagen synthesis by fibroblasts. 17,18,19 The development of the porcine overstretch balloon injury model of restenosis has provided an excellent model in which to evaluate new therapies since as radiation. 20 In this animal model one or more of the coronary vessels are subjected to overstretch balloon injury and at two weeks, four weeks or six months the animal is sacrificed and the vessels harvested.…”
Section: Introductionmentioning
confidence: 99%